Estratégias para a mudança de comportamento relacionado à reciclagem: protótipo de artefato tecnológico para coleta seletiva de resíduos sólidos urbanos - Campello, Romildo de Pinho (2024)
Despite the National Solid Waste Policy (PNRS), established in 2010, the management of recyclable waste in Brazil still faces significant challenges. The practice of recycling, the engagement of the population and the management instruments remain insufficient and ineffective. This dissertation proposes to evaluate the impact of the application of a behavioral public policy, using a technological artifact as a strategy to increase the participation of the population in the selective collection of urban solid waste. To this end, three main studies were developed. The first study reviewed methodologies for changing habits in waste management, identifying effective strategies for sustainable practices adapted to the local context, providing a theoretical basis for large-scale practical interventions. The second study investigated the use of nudge strategies in the design of applications and human- computer interfaces, analyzing how these small interventions, which influence behavior without restricting choices, were applied to promote desirable behaviors such as recycling. The review included examples of success and lessons learned, offering insights for the development of new technological tools. Both studies were conducted through a Systematic Review of the Literature. The third study aims to develop the prototype of a technological artifact as a strategy to increase the participation of the population in the selective collection of urban solid waste, by incorporating nudge strategies and exploring the social dynamics based on the model of Axel Honneth, which analyzes social recognition through love, right and solidarity, and Nancy Fraser's with the dimension of redistribution. The prototype of the artifact, designed by the Design Science Research (DSR) method adapted for small-scale studies, aims to facilitate waste separation, contribute to the environmental education of users and encourage them with rewards and positive feedback. The interface is designed to be accessible and intuitive and ensure effective use by everyone. In this way, it enables the creation of solutions that align economic growth and environmental preservation, strengthening social responsibility and community engagement in building a more sustainable future.